(untitled) (Bangladesh Journal of Urology, 2020)
Introduction: Anastomotic urethroplasty is the treatment of choice for posterior urethral distraction defect. To notice the high failure rate of anastomotic urethroplasty, several peri-operative factors are identified. Among the per-operative factors, mucosal fixation of the both urethral ends is one of the outcome influencing factor that is recently identified. So, this randomized clinical trial has been designed to compare the outcome of anastomotic urethroplasty in posterior urethral distraction defects with or without mucosal fixation. Objective: To compare the outcome of anastomotic urethroplasty of PUDD patient groups with or without mucosal fixation in terms of post-operative IPSS, maximum urine flow rate and post void residual urine. Patients and Methods: The present study was conducted in the department of Urology, BSMMU between January’16 - November’17. Posterior urethral distraction defects with length of gap between two urethral segments upto 3 cm. were included in the study. The patients in whom anastomotic urethroplasty were done with mucosal fixation were enrolled as study group(n=21) and patients in whom anastomotic urethroplasty were done without mucosal fixation were included as control group(n=21). All the patients were followed upto 6 months of anstomotic urethroplasty and failure of anastomotic urethroplasty (by RGU and MCU), PVR and maximum urine flow rate (Qmax) in between two groups were compared. Result: The failure rate was found significantly higher in control group than in the study group (p=0.043). The control group showed highly significant (0.001) increase in postoperative PVR than the study group and the study group showed significant (0.007) increase in post operative maximum urine flow rate than the control group as was assumed in the hypothesis. Conclusion: In conclusion, it can be said that anastomotic urethroplasty with mucosal fixation is a better option than anstomotic urethroplasty without mucosal fixation. But multicentric trial is needed to further comment. Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.31-34